The Development and Competition of Cinemas in Jakarta, 1950-1966 - Mitalia, Ghesa Ririan (Indonesian Historical Studies, 2023)
The return of Jakarta as the capital of the Republic of Indonesia was followed by significant developments. The development of Jakarta cannot be separated from the massive increase population. Jakarta is also going through numerous infrastructure developments as well as the resurgence of its entertainment industry, particularly cinemas. This article questions, why cinemas in Jakarta experienced their ups and downs during 1956-1966 and how could be it survived through the difficult times? The period 1950-1966 become a unique period for Indonesia because of the influx of pop-cultures and trends from the west amidst the euphoria of nationalism. In the mid of the surging nationalism after the revolutionary, the western culture had entered and become trend among young people. The cinemas in Jakarta were gaining popularity with the large number of western films (Hollywood). However those paradoxical situation then developed into a political problem. Imported films were deemed not in accordance with the nation’s character and contradicted to the revolution’s spirit so they needed to be banned. It was actually connected to the nation’s situation at that time, which was currently in conflict with Malaysia and the United States of America. This political conflict escalated in the early 1960s and subsided after the Coup Attempt of 30 September Movement. Those conflicts made Jakarta’s cinemas suffered a difficult time. The absence of imported films, especially from India, Malaysia and Hollywood, had an effect on the declining number of spectators. However, it was surprisingly emerged another entertainment genre such as Sandiwara which gaining popularity. During 1960s, cinemas in Jakarta not only had to deal with the political issues but also had to compete with Sandiwara.